High Motor Cortex Excitability in Highly Hypnotizable Individuals: A Favourable Factor for Neuroplasticity?. (15th March 2020) - Spina, Vincenzo; Chisari, Carmelo; Santarcangelo, Enrica L.
Highlights: Motor imagery induces ideo-motor behavior in highly hypnotizable subjects ( highs ). This can be due to strong functional equivalence (FE) between imagery and perception. Stronger FE could be sustained by greater excitability of the highs' motor cortex. TMS supports this hypothesis comparing highs with low/medium hypnotizables subjects. Imagery training and neuroplasticity could be more effective in highs . Abstract: Hypnotizability is a psychophysiological trait associated with morphofunctional brain peculiarities and with several cognitive, sensorimotor and cardiovascular correlates. Behavioral and EEG studies indicate stronger functional equivalence (FE) between motor imagery and action in the individuals with high hypnotizability scores ( Highs ). We hypothesized that stronger FE leading to greater proneness to ideomotor behavior could be due to greater cortical excitability of the motor cortex. The aim of the study was to evaluate the motor cortical excitability through measurements of the muscle potentials (MEPs) evoked in the left abductor pollicis brevis by transcranial magnetic stimulation (TMS) of the right motor cortex in 10 Highs, 10 medium ( Mediums ) and 10 low hypnotizable individuals ( Lows ) classified according to the Stanford Hypnotic Susceptibility Scale, form A (SHSS). They were studied in basal conditions (B) and during motor imagery (MI). Results showed significant, negative correlations (i) between hypnotizability and MEPs Resting Motor Threshold (RMT) in basal conditions, and (ii) between hypnotizability and both MEPs RMT and suprathreshold (I1mv ) stimulation intensities during MI. ANOVA revealed significantly lower stimulation intensities in Highs than in Lows, with Mediums exhibiting intermediate values. Thus, the Highs' greater cortical excitability could sustain their greater FE and proneness to ideomotor behavior. In cognitive neuroscience these findings are relevant to the physiological interpretation of the response to sensorimotor suggestions by participants in the ordinary state of consciousness. In the clinical field they can predict the efficacy of mental training based on motor imagery and, possibly, the degree of imagery-induced cortical plasticity.